The Beveridge report and the health services
1943 1943 1940s 2 pages THE BEVERIDGE REPORT and THE HEALTH SERVICES Health for All. That every man, woman and child should be given the opportunity to be born healthy, to live in health and to enjoy life with as little fear of disease and ill-health as modem medical science can assure, is an aim worthy of our greatest efforts. It is that aim that lies behind the Beveridge Report's attempt to abolish poverty, for healthfulness is impossible without adequate nourishment ; it is that aim that was in the mind of Sir William Beveridge when he framed his famous Assumption B. that after the war there will exist a full "comprehensive national health service available to all." Assumption B is an indication of a necessity of modern times; it hints only at the method to be adopted to make the assumption a reality; but it asks for a form of service which can be provided, as "The Socialist Programme for Health" issued by the Socialist Medical Association shows, by very simple, efficient and inexpensive means. What does the Worker get Now? What kind of medical service does the worker get to-day? Except in very few cases he gets an incomplete service, provided in a variety of ways, many costly, some inefficient and few under proper democratic control. The "Panel" provides a General Practitioner for the insured worker but nothing for the wife and dependents. It provides no form of institutional treatment and very little in the way of specialist advice for anybody. Hospital treatment may be obtained at voluntary or municipal hospitals, and usually has to be paid for, at least in part, by payments in advance to a contributory scheme or afterwards by assessment. Rehabilitation, the restoration to as great a degree of physical efficiency as possible, is available only for certain cases and suitable conditions for convalescence are often impossible, while the whole business of being ill is a nightmare to the man with a family dependent on him and a great strain on a family's resources. What should the Worker Get? What should a "comprehensive national health service" provide for every citizen? If properly planned it should provide every necessary medical service in health, sickness or injury, should comprise every possible form of medical advice and treatment, should be available in the home and in hospitals, should be without "economic barrier to delay recourse to it," and should be available equally in every part of the country. It should provide all medicines, appliances and apparatus and should check every feature of the environment that is disadvantageous to health, so that every citizen would have the chance to maintain his or her bodily efficiency or to recover it when it has been lowered by any cause. All this should be provided by a simple financial system, the cost spread over the whole nation, and without any distinction on 126/TG/377/1/1/123